A PROPOSED SCENARIO FOR THE SELECTION OF AGRICULTURAL EXTENSION MANAGERS IN THE GOVERNORATES OF THE CENTRAL REGION OF IRAQ - & AL-CANAY, AL-SAADY (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this research was to develop a proposed Conceptualization for the requirements of selecting agricultural extension managers in the governorates of the central region of Iraq and to identify the opinions of the respondents regarding the proposed Conceptualization. To achieve the research objectives, the proposed sampling scale was prepared for the selection requirements of agricultural extension managers in the light of the relevant literature, Of the proposed Conceptualization, and then present the proposed scale of vision to a group of experts in the field of agricultural management and extension to explore their views on the components of the proposed scenario (areas, paragraphs) and verify its validity and determine the proportion of agreement (75%) and more of the views of experts The presentation of the proposed requirements for the selection of agricultural extension managers was completed in its first modified form, consisting of (73) paragraphs divided into (6) areas: 1. Fundamentals of selection of managers 2. Personal characteristics - 3) Human relations 4) Decision making 5 - Technical skills 6 - Creativity. The research was conducted on the governorates of the Central Region (8) Governorates. The Governorates of AL-Anbar and Salahuddin were excluded for the poor security situation. By (70%) and by (4) provinces (Baghdad, Babylon, and the data were collected from the respondents by means of the questionnaire and in the personal interview method to indicate the degree of their approval of the proposed areas and areas of the proposed scenario. The final form of the paragraphs and areas was reached. The proposed scenario for the selection of agricultural extension managers using the following criterion: The paragraph shall be within the final form of the proposed scenario if it obtains a weighted mean greater than the mean of the scale of the approval scale used in the research of (3) degrees. In the final form of the proposed conceptualization for each of them to obtain a weighted mean greater than the mean of (3) degrees. Therefore, the researcher recommended that the competent authorities (the directorates of agriculture in the governorates, extension and agricultural training department) In order to improve and develop the administrative work of the agricultural extension system.